Antibacterial Activity and Mechanism of Lacidophilin From Lactobacillus pentosus Against Staphylococcus aureus and Escherichia coli - Zhu, Yinglian; Zhang, Shuang (Frontiers in Microbiology, 2020)
The main purpose of this study was to explore the antibacterial activity and mechanism of lacidophilin from Lactobacillus pentosus against Staphylococcus aureus and Escherichia coli. The effects of temperature, enzyme, metal ions, and pH on the antibacterial activity of L. pentosus were evaluated. The result showed that lacidophilin had good thermal stability and could be decomposed by trypsin completely. The antibacterial ability was affected by high concentration of metal ions, and the best antibacterial ability was acquired under acidic conditions. The antibacterial mechanism of lacidophilin was explored through studying cytomembrane injury, phosphorus metabolism, protein changes, and oxidative stress response of the indicator bacteria. It was shown that lacidophilin destroyed the cytomembrane of the bacteria and increased the cytomembrane permeability, which resulted in the leak of proteins, nucleic acids, and electrolytes. In addition, it further restrained phosphorus metabolism, caused changes of some protein contents, and increased cytomembrane lipid peroxidation and cell oxidative damage. All these might inhibit the growth of bacteria and even cause their death. This study identified a natural biological preservative with strong antibacterial activity against both Gram-positive and Gram-negative foodborne pathogens. The high antibacterial activity against the two types of bacteria reflected its potential in food preservation used as a natural food preservative.